Judging a product by its cover: Packaging sustainability and perceptions of quality in food products. (October 2016) - Magnier, Lise; Schoormans, Jan; Mugge, Ruth
Highlights: Packaging sustainability positively influences perceptions of food product quality. Product sustainability moderates the positive effect of packaging sustainability. Product naturalness explains the perceptions of product quality. Abstract: In this paper, we test the influence of packaging sustainability on consumers' perceived quality of food products using two experiments featuring raisins, chocolate bars and coffee. First, the results show that the perceived quality of a food product is more positive when it is packed in a sustainable packaging than when it is packed in a conventional packaging. Next, we demonstrate that product sustainability moderates the influence of packaging sustainability. Finally, we show that the perceived naturalness of the product induced by package and product sustainability explains the perception of product quality.